O campo de energia elétrica no Brasil - de 1880 a 2002 - Gomes, João Paulo Pombeiro (2005)
Since electric power is an essential element in modern society, this paper analyzes the historic and institutional factors that have contributed to the formation and organization of the Brazilian electric sector, from the time when it started to be used in this country until the end of year 2002. This analysis is based on a linear description of historic facts, giving emphasis to crucial events ¿ or critical incidents, as they were called for the purpose of this paper. As to these happenings, the social actors who played an important role in the development of the Brazilian electric power sector were analyzed. An analytical model based on the theoretical references offered by the Institutional Theory was used. The study also highlights the elements that comprehend the development of the phenomenon in face of the ambivalence existing in a developing country, which is the case of the Brazilian electric power sector. The organizational fields that were established at the time determined by the main crucial incidents presented throughout the length of time covered by this study. The resources that the main social actors involved in the electric power sector may use by are also identified, as well as their main interests and level of influence these actors may have. Several documents were analyzed. The qualitative methodology was used. Also, many semi-structured in-depth interviews of the people who have made the history of this sector for reliability were conducted. Finally, this study includes the main elements that have shaped the institutional model of the Brazilian electric sector. It also characterizes the external environment as the element which has most influenced the sector and has also led its way throughout the different developmental phases, especially with respect to funding. The growing rates of power consumption indicate the need for a constant increase in the supply of electric power to meet the needs of society and economic development. This requires constant investment. Lack of investment is a limiting factor. Not only does it hinder the development of the country but it may also result in very unfortunate mishaps such as electric power rationing, such as the kind we had to endure a while ago.